An Ultrahigh‐Resolution Digital Image Sensor with Pixel Size of 50 nm by Vertical Nanorod Arrays. (1st July 2015) - Jiang, Chengming; Song, Jinhui
<x xml:space="preserve">Abstract</x> The pixel size limit of existing digital image sensors is successfully overcome by using vertically aligned semiconducting nanorods as the 3D photosensing pixels. On this basis, an unprecedentedly high‐resolution digital image sensor with a pixel size of 50 nm and a resolution of 90 nm is fabricated. The ultrahigh‐resolution digital image sensor can heavily impact the field of visual information.